(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2019)
Abstract: This article deals with the Maintenance Fund Boards and Basic Education Development and the Education Professionals Appreciation - Fundeb in Northeastern municipalities, analyzing the municipal education secretaries and the counselors perceptions about their roles in such social participation and representation spheres. The research analyzes the counselors acting dynamic in the municipalities considering the FUNDEB Board as an integral (and important) part of the municipal educational administration. This study is a cut of a Joaquim Nabuco Foundation / MEC survey from 2015 with 382 municipalities, using questionnaires applied to every education secretaries in the survey and to 2,605 Fundeb Board Members. The present article refers to the results that discuss such subjects perceptions about social representation and participation, in the context of Brazilian cooperative federalism, which is characterized by decentralizing the educational services and, in fact, provides an imbalance between the subnational federated entities and the federal sphere with significant effects on the local educational policies management. Keywords: Fundeb Boards. Social Participation and Representation.